1, 25(OH)2D3 alleviates LPS-induced preeclampsia-like rats impairment in the protective effect by TLR4/NF-kB pathway. (December 2022) - Ma, Yantuanjin; Yang, Yuling; Lv, Mengxin; Zhang, Yuhang; He, Qiuyue; Zhang, Yaqin; Su, Hong; Deng, Xingli; Qian, Yuan
Abstract: Introduction: Accumulating epidemiological studies support that Vitamin D deficiency is associated with the pathogenesis of preeclampsia. However, it is unknown whether vitamin D can be used as a treatment for preeclampsia. This study aimed to explore whether vitamin D supplementation could improve the rat model of preeclampsia. Methods: LPS was used to establish a rat model of preeclampsia. Inflammatory cytokines were examined by QRT-PCR and ELISA assays, and the concentration of sfit-1 and NO was assessed by ELISA. Analyzing the pathological features of the placenta with hematoxylin-eosin. The spatial learning and memory abilities of offspring were evaluated by the Morris water maze. Immune histology and western blot were performed to evaluate the expression levels of inflammatory pathway-associated Factor and vascular endothelium-associated Factor in the placenta. Results: Vitamin D treatment reduced the blood pressure and urine protein of PE model rats, alleviated pathological damage to the placenta and pregnancy outcomes, and protected PE offspring from impaired memory and learning abilities. Moreover, TLR4 signaling pathway in the placenta was inhibited. Furthermore, vitamin D supplementation increased the expression of endothelial growth factor and vascular relaxing factor, and there was no significant difference compared with the control group. Discussion: We generated the result that Vitamin D supplementation significantly improved the phenotype of preeclampsia and adverse pregnancy outcome caused by an abnormal inflammatory reaction and endothelial dysfunction in the placenta, and improved the learning and cognitive ability of offspring. Highlights: Vitamin D improved blood pressure, proteinuria and adverse pregnancy outcomes. In LPS-induced preeclampsia rats. Vitamin D supplementation improved the learning and memory ability of offspring of preeclampsia rats. Vitamin D suppressed overactivation of TLR4 signaling pathway and attenuated elevated inflammatory cytokines. Vitamin D improves placental vascular endothelial function.